2005
DOI: 10.3354/meps295279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fine-scale oceanographic features on the distribution and movements of harbour porpoises Phocoena phocoena in the Bay of Fundy

Abstract: We describe an integrative approach to studying the fine-scale distribution of harbour porpoises Phocoena phocoena in the Bay of Fundy, using satellite telemetry, line transect surveys and remote sensing techniques. Analysis of satellite telemetry data from 6 porpoises (5 male, 1 female) revealed that over the course of a month individuals ranged across large areas (7738 to 11 289 km 2 ) but concentrated their movements in small focal regions (August mean = 294 km 2 , September mean = 252 km 2 ), often proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 68 publications
6
132
0
Order By: Relevance
“…In the UK and eastern Canada, harbour porpoise distribution correlates with prey distribution, frontal zones, water depth and other environmental variables (Santos et al 2004, Johnston et al 2005, Goodwin 2008, Bailey & Thompson 2009, Isojunno et al 2012. The importance of environmental factors such as currents, chlorophyll and nutrients was also confirmed by Danish and German studies (Edrén et al 2010, Gilles et al 2011, Sveegaard et al 2012a.…”
Section: Seasonal Occurrence and Trends In Harbour Porpoise Presencementioning
confidence: 76%
“…In the UK and eastern Canada, harbour porpoise distribution correlates with prey distribution, frontal zones, water depth and other environmental variables (Santos et al 2004, Johnston et al 2005, Goodwin 2008, Bailey & Thompson 2009, Isojunno et al 2012. The importance of environmental factors such as currents, chlorophyll and nutrients was also confirmed by Danish and German studies (Edrén et al 2010, Gilles et al 2011, Sveegaard et al 2012a.…”
Section: Seasonal Occurrence and Trends In Harbour Porpoise Presencementioning
confidence: 76%
“…Speckman et al (2005) found the highest densities of herring and longfi n smelt in warm waters <40 m deep, but herring peaked in clearer, more saline waters while longfi n smelt peaked in more turbid, fresher waters. Johnston et al, 2005;Marubini et al, 2009;Gilles et al, 2011). Given schooling prey occupy a range of oceanographic domains in the lower inlet, this may explain some of the interannual variability in harbor porpoise encounter rates in offshore versus nearshore areas during systematic surveys (e.g., NMFS beluga whale survey data).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that core areas of dolphin use are related to the foraging (Hastie et al, 2004;Johnston et al, 2005). Indeed, the Caravelas River mouth was used intensively by Guiana dolphin groups while foraging, and, for this reason, may be regarded as a critical habitat for the species in the region.…”
Section: Discussionmentioning
confidence: 99%